A University as a Driving Force of Ecological Initiatives for Society - Sobczyk, Wiktoria; Ciepiela, Maciej (Journal of Education, Technology and Computer Science, 2021)
This paper emphasizes the role of universities in encouraging ecological initiatives for sustainable development. We characterized the origin of sustainability and its consistency with the Constitution of the Republic of Poland. Moreover, we present ecological education as the concept of lifelong learning in the spirit of respect for the natural world. The examples of pro-ecological higher education initiatives were described, such as Poznan School of Logistics (“EKO-LOG” programme), Jan Kochanowski University of Kielce and the University of Social and Medical Sciences in Warsaw (education of ethnic minorities), Andrzej Frycz-Modrzewski Krakow University and the University of Agriculture in Krakow (Friend of the National Park educational program) as well as the AGH University of Science and Technology (continuing education). It has been shown that schools and universities play a major role in environmental education not only for children, but also adults. It is worth mentioning that the potential and clout of universities should be continuously employed in the environmental movement.